McDonald’s Customer’s Satisfaction Strategies during COVID-19 Pandemic in Malaysia - Friday Ogbu Edeh; Ranjith P V; Nurul Syafawani; Daisy Mui Hung Kee; Nurul Aina; Nurul Syafikah; Nurunnisa Nurunnisa (AIBPM Publisher, 2021)
Generally, McDonald’s is recognized as one of the most successful brands worldwide. They are well-known throughout the world for their popular fast food, especially burgers. However, COVID-19 pandemic has impacted various economic sectors, including Food Beverage. McDonald’s sales have also been impacted when COVID-19’s lockdown restricts the dine-in operation and limits the customer’s satisfaction due to the SOP. Thus, this research aims to identify and analyze the strategies implemented by McDonald’s to increase the customer’s satisfaction during Covid-19 pandemic. To find out the result of the research, a survey has been conducted and the data was collected from individuals with different age and income ranges in Malaysia. A total of 100 individuals have participated in this survey. Besides, in order to gain a better understanding of our study, secondary data for this study was gathered from a variety of websites, journals, and articles. The findings of this research indicate that McDonald's decision to increase the Food Safety measure is by implementing various safety requirements. This is the most successful approach to improve customer’s satisfaction during COVID-19. They chose this strategy to demonstrate their commitment to preserve a healthy life.